Primary malignant giant cell tumor of the patella: report of a rare case (Faculty of Medicine Universitas Indonesia, 2013)
Primary malignant giant cell tumor (GCT) at the patella bone is a very rare case. It is a high-grade sarcoma characterized by a lesion in which there are areas of synchronous high-grade sarcomatous next to areas of benign GCT. A limb sparing approach is applicable to virtually any bone lesion, whether low grade or high grade. We report a case with primary malignant GCT at the patella, from diagnostic to detailed limb sparing surgery procedure. Fifteen months after surgery, the patient had a good functional outcome without local recurrence and distant metastasis. (Med J Indones. 2013;22:238-42. doi: 10.13181/mji.v22i4.607)